OPTIMALISASI MUTU PENDIDIKAN PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN LEMBAGA MELALUI PENERAPAN CONTINUOUS IMPROVEMENT DALAM TOTAL QUALITY MANAGEMENT - Dewi, Sandra; Br. Saragih, Evi Susi Sandrawita; Rujianto, Rujianto; Azainil, Azainil; Komariyah, Laili (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
This study aims to analyze the optimization of educational quality through the implementation of the continuous improvement principle within the framework of Total Quality Management (TQM) in the Accounting and Financial Institution (AKL) Program at SMKN 4 Penajam Paser Utara. This research employed a qualitative approach with a descriptive research design. Data were collected through observations, in-depth interviews, and documentation studies involving the principal, head of the AKL program, vocational teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings revealed that the implementation of continuous improvement was carried out continuously in four main aspects: program management, administration and finance, resources, and learning processes. In program management, quality improvement was achieved through program evaluation, curriculum development aligned with industry needs, and strengthening partnerships through the Mini Bank Teaching Factory in collaboration with Bank BTN. In administration and finance, the school utilized digital systems such as ARKAS and Dapodik to support effective, transparent, and accountable governance. In terms of resources, quality enhancement was supported by adequate facilities and infrastructure as well as continuous professional development for teachers. In the learning process, the implementation of the Mini Bank Teaching Factory, industrial visits, and guest teacher programs improved both technical and non-technical competencies while strengthening the link and match between education and industry. The study concludes that the implementation of continuous improvement within the TQM framework contributes significantly to improving educational service quality, aligning learning with industry needs, and enhancing the competitiveness of graduates in the AKL program.